Thermal Analysis of VLSI System: A Computational Fluid Dynamics Approach - Fauzi, Mohamad Nasaruddin (2017)
Compact size of Very Large Scale Integrated (VLSI) system recently causing the rising of the on-chip power densities and later will increase the temperature of the system. The increase in temperature will eventually affects the clock frequency of the system and makes the timing setup of the component unstable. These problems lead to lowering the reliability and performance of the system. The designers must get the thermal profile of the systems in order to know the temperature distribution, estimate the power distribution of the system and to understand the leakage reduction. In this study, Silicon die is focused as VLSI product because it is the main component for Integrated Circuit (IC). Then, in this study, appropriate Computational Fluid Dynamics (CFD) modelling of VLSI system for detecting thermal profile is discussed. This study concentrates on analysing the thermal profile of a VLSI system under transient state condition using CFD approach. In CFD approach, ANSYS software is used because of the accessibility and simple configuration. For the simulation based on ANSYS, the workbench module was used. From the results obtained, it can be observed that maximum temperature distributed on the middle of the model, which is on silicon chip. This is the important part where the VLSI designer should focus more during the design process of VLSI system. Method of using CFD for thermal analysis is able to overcome the limitation of current monitoring system. It can predict the temperature distribution of an IC chip for the next time level without being access to the die.